Respostas da canola à elevação do lençol freático e à restrição de radiação solar - Monteiro, Eduardo Castiglioni (2022)
The canola crop (Brassica napus L.) has great economic importance, due to the high quality of its oil and high protein content in its grains. As its cultivation takes place in winter, there are extensive idle areas of floodplains in subtropical environments in Brazil that could be used for cultivation, provided that the excess water in the soil is controlled by the increase in the water table. In this region, there is also greater cloudiness in winter, which may also limit the expression of the crop's productive potential by reducing the availability of solar radiation. Therefore, the objective of this work was to evaluate the effect of the elevation of the water table and the restriction of the availability of solar radiation in the reproductive subperiod of canola on growth, development and grain yield. The experiments were carried out in a greenhouse with automated opening management, located in the Department of Plant Science at the Federal University of Santa Maria (UFSM). The design used was completely randomized (DIC) with six replications, and in 2019 six levels of water table depth (0, 50, 100, 150, 200 and 250 mm) were evaluated. In 2021, two factors were evaluated, two levels of factor A - restriction of availability of solar radiation (0 and 50% restriction) inside the greenhouse and four levels of factor D - depth of the water table (0, 85, 170 and 255 mm), totaling eight treatments. The Diamond hybrid was sown in July 2019 and May 2021 in drip irrigated pots. Each experimental unit consisted of a vase with a volume of 20 liters with three plants, filled with soil of the Brown-Agrey Argisol class. Permanent maintenance of the depth of the water table from the beginning of flowering to the end of the crop cycle was possible by making siding boxes according to the dimensions of the pots, where the inside of the boxes was lined with three layers of plastic film. to accumulate water. To impose the restriction on the availability of global solar radiation (Rg) in 2021, a structure with black raffia screen (50%) was made on and around the plants. The environmental conditions, the growth and the production of the plants were evaluated and the data analyzed using the Software R with the ExpDes package, with 5% of significance in the statistical tests. Greater plant heights (AP) occur at depths of 150 and 170 mm and greater average leaf areas per plant (AFM) occur at depths of 170 and 250 mm of water table. Grain yield was not influenced by the availability of solar radiation during the reproductive period. In general, the water table depths of 250 mm and 255 mm in the environmental conditions of 2019 and 2021, respectively, provided better growth and development conditions for canola plants. The maintenance of the water table at greater depths, through the drainage of lowland soils, is important and necessary as one of the necessary factors for the expansion of the culture to occur in these areas.